From creep to flow: Granular materials under cyclic shear - Yuan, Ye; Zeng, Zhikun; Xing, Yi; Yuan, Houfei; Zhang, Shuyang; Kob, Walter; Wang, Yujie (Nature communications, 2024)
When unperturbed, granular materials form stable structures that resemble the ones of other amorphous solids like metallic or colloidal glasses. Whether or not granular materials under shear have an elastic response is not known, and also the influence of particle surface roughness on the yielding transition has so far remained elusive. Here we use X-ray tomography to determine the three-dimensional microscopic dynamics of two granular systems that have different roughness and that are driven by cyclic shear. Both systems, and for all shear amplitudes Γ considered, show a cross-over from creep to diffusive dynamics, indicating that rough granular materials have no elastic response and always yield, in stark contrast to simple glasses. For the system with small roughness, we observe a clear dynamic change at Γ ≈ 0.1, accompanied by a pronounced slowing down and dynamical heterogeneity. For the large roughness system, the dynamics evolves instead continuously as a function of Γ. We rationalize this roughness dependence using the potential energy landscape of the systems: The roughness induces to this landscape a micro-corrugation with a new length scale, whose ratio over the particle size is the relevant parameter. Our results reveal the unexpected richness in relaxation mechanisms for real granular materials. Granular materials exhibit yielding behaviors rather different from glasses that can be elastic. Here, Yuan et al. show a cross-over from creep to diffusive dynamics in three-dimensional granular systems under cyclic shear and that the relaxation process depends on the roughness of the constituent particles.